Involvement of the drosophila taurine/aspartate transporter dEAAT2 in selective olfactory and gustatory perceptions. - Besson, M.T.; Sinakevitch, I.; Melon, C.; Iché-Torres, M.; Birman, S. (Journal of Comparative Neurology, 2011)
Excitatory amino acid transporters (EAATs) are membrane proteins involved in the uptake of neurotransmitter amino acids in the nervous system. The Drosophila dEAAT2 gene was previously described to encode a taurine/aspartate transporter. To analyze further the expression pattern and physiological function of this protein, we generated transgenic flies containing either the dEAAT2 promoter region fused to GAL4 (dEAAT2-GAL4) or a transgene allowing expression of a dEAAT2::GFP fusion protein (UAS-dEAAT2::GFP). We observed that dEAAT2-GAL4 expresses green fluorescent protein (GFP) in neurons in central and peripheral structures of third-instar larvae and adult flies. Labeled neurons were found in olfactory and gustatory pathways, in which dEAAT2::GFP was detected from the dendrites of the sensory neurons up to the first- and second-order centers. dEAAT2-GAL4 is also expressed in mechanosensory neurons. We found that a viable piggyBac insertion strain disrupts dEAAT2 expression. This mutant appears morphologically normal and presents no locomotor or phototaxis impairments; however, its brain taurine level is significantly reduced compared with that of wild-type flies. The dEAAT2 mutant showed decreased avoidance behavior in the presence of high concentration of propionic acid compared with wild-type flies, but no modification of the avoidance response to benzaldehyde. In gustatory tests, both mutant and control flies were normally attracted to sucrose; however, the dEAAT2 mutant presented a higher salt sensitivity, being repulsed by low and high salt concentrations. Therefore, we conclude that dEAAT2 does function as a taurine transporter in vivo and that this protein is physiologically required for the sensory perception of specific environmental molecules.